Preference of Mother Tongue for Effective Understanding of Covid-19 Pandemic Disease in Three Selected Local Governments in Jigawa State of Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study examined the preference of Mother Tongue (MT) for effective understanding of the COVID-19 pandemic in three selected Local Government Areas of Jigawa State, Nigeria. Two research questions were formulated to guide the study. The population consisted of residents from the three selected Local Government Areas, from which 215 respondents were randomly sampled. A structured questionnaire developed by the researcher served as the main instrument for data collection. The collected data were analyzed using frequency and percentage. The findings of the study revealed that the respondents prefer the use of Mother Tongue (MT) for effective understanding of COVID-19 disease in both social and official settings. It further showed that communication in MT through radio and mobile phones facilitates effective understanding of the COVID-19 pandemic. The study recommended, among others, that public health campaigns and awareness programs should adopt local languages to improve the effectiveness of health communication, especially in rural communities where literacy levels are low. In addition, government at all levels should ensure timely procurement of all relevant facilities to fight the pandemic disease when it emerges.